Effect of bacterial nanocellulose binding on the bactericidal activity of bovine lactoferrin. Issue 7 (July 2020) - Padrão, Jorge; Ribeiro, Sylvie; Lanceros-Méndez, Senentxu; Rodrigues, Lígia R.; Dourado, Fernando
Abstract: Bovine lactoferrin (bLF) has been extensively described as a wide spectrum antimicrobial protein. bLF bactericidal activity has been mainly attributed to two different mechanisms: environmental iron depletion and cell membrane destabilization. Due to its antimicrobial properties, bLF has been included in the formulation nutraceutical food products and edible active packages. This work comprises the experimental evidence of the requirement of bLF unrestricted mobility ("free bLF") to effectively perform its bactericidal action. To assess the unrestricted and restricted bLF activity, a nontoxic matrix of bacterial nanocellulose (BNC) was used as carrier, and as an anchoring scaffold, respectively. Therefore, BNC was functionalized with bLF through two different methodologies: (i) bLF was embedded within the three-dimensional structure of BNC and; (ii) bLF was covalently bounded to the nanofibrils of BNC. bLF efficiency was tested against two bacteria isolated from clinical specimens, Escherichia coli and Staphylococcus aureus . bLF concentration after covalent binding to BNC was two-fold higher in comparison to the embedding method. Nevertheless, only the embedded bLF exhibited a significant bactericidal activity, due to bLF ability to permeate the BNC matrix and execute its bactericidal action. Abstract : Materials science; Food technology; Microbiology; Bacterial nanocellulose; Bovine lactoferrin; Antibacterial protein activity